AUTOMEDICAÇÃO EM IDOSOS: MEDIDAS DE PREVENÇÃO E CONTROLE - Fernanda Lorena Pereira Rocha Beserra; Valéria Ferreira da Costa Borba; Jáfia Elana Gonçalves Torres; Sara Nayara Duarte da Silva; Mellyssa Ayêska Custodio Sobreira Macedo (Revista Contexto & Saúde, 2019)
RESUMO